Embedding cultural studies in public health higher education: the role of medical anthropologists. (2022)
Medical Anthropology is a body of knowledge with universal application. It bridges the gap between socio-cultural elements and public-health challenges; as a result, many medical anthropologists have raised the importance of culture in health matters. While public health pedagogy revolves around the ‘Germ Theory’ and the biomedical explanations of disease and illnesses; it is also very important to put the bio-sociocultural phenomena of health into consideration through an in-depth understanding of the social-cultural dimensions of health, healthcare and health-management. This is because ethnographic conceptions and the understanding of diseases, illnesses and wellbeing are germane to the success of public health. Embedding medical anthropological epistemology and research methods in public health higher education in Nigeria will contribute to the advancement of medical training through the use of ethnographic epistemology and methods, whereby vivid case studies of the social-cultural dimensions of public health issues would be subjected to critical discourse in the classroom. Utilizing ethnographic epistemological and methodological research cum pedagogical approaches in public health higher education will yield considerable success